Improvement of milk yield and quality with supplemental feeding of Azolla - K, Giridhar; S, Senani; G, Letha Devi; DT, Pal; A5, Arangasamy; A, Mech; Kataktalware, M A; GB, Manjunath Reddy; N, Narayanaswamy B; L, Niketha (Indian Farming, 2020)
Field evaluation was done with Azolla as supplemental feed on the milk production and economics under Farmer First Program of ICAR. About 1100 grams of fresh Azolla was fed to the cows daily and milk yield was continuously recorded for 7 weeks. The dry matter content of Azolla varied between 4.7 and 5.0% and the crude protein from 22.9 to 23.5%. Azolla supplementation for 7 weeks improved the mean daily milk production from each cow by 0.6 liters, and milk fat from 3.3 to 3.5. The supplementation of Azolla improved monthly income from milk sale by over ` 500 per cow. This low cost technology can easily be adopted by small dairy farmers to improve their profits.